The effect of subjective life expectancy on the participation in commercial pension insurance of Chinese elderly - Zhou, Mei; Wang, Yingyi; Liang, Yunjia; Shi, Ruonan; Zhao, Shaoyang (Frontiers in Psychology, 2022)
Objective: This paper studies the impact of the subjective life expectancy of the elderly on their commercial pension insurance participation at micro perspective, providing new evidence to explain the motivation of commercial pension insurance participation in China. Methods: Using 4 waves of data from China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2018, a multiple linear regression model is constructed to investigate the effect of subjective life expectancy on commercial pension insurance participation among Chinese elderly, and IV model estimation shows that the results are robust. Meanwhile, the heterogeneity of the effect of elderly life expectancy on commercial pension insurance participation behavior among different characteristic groups is also studied. Results: A one standard deviation improvement in our measure of subjective life expectancy predicts a 0.9 percentage point higher participation rate in commercial pension insurance. We also find that there is significant heterogeneity in the effects of subjective life expectancy on the participation of elderly people in commercial pension insurance with respect to gender, education, hukou, and wealth. Conclusion: This paper provides a new perspective to explain the factors influencing commercial pension insurance participation in China. We suggest that improving residents' awareness of life expectancy is beneficial to their reasonable retirement planning, in the background of stepping into an aging society in China.